2007
DOI: 10.1186/1471-2288-7-46
|View full text |Cite
|
Sign up to set email alerts
|

The CUSUM chart method as a tool for continuous monitoring of clinical outcomes using routinely collected data

Abstract: Background: The lack of robust systems for monitoring quality in healthcare has been highlighted. Statistical process control (SPC) methods, utilizing the increasingly available routinely collected electronic patient records, could be used in creating surveillance systems that could lead to rapid detection of periods of deteriorating standards. We aimed to develop and test a CUmulative SUM (CUSUM) based surveillance system that could be used in continuous monitoring of clinical outcomes, using routinely collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 14 publications
0
48
0
Order By: Relevance
“…The AL and UCL calculations are based on Gan (1991) abacus, in function of ARL (Average Run Length) value for both situations and the reference value k. In this study a significance level The CUSUM charts has a higher and consistent sensibility to parameters values variation. (Sibanda & Sibanda, 2007) …”
Section: Phasementioning
confidence: 99%
“…The AL and UCL calculations are based on Gan (1991) abacus, in function of ARL (Average Run Length) value for both situations and the reference value k. In this study a significance level The CUSUM charts has a higher and consistent sensibility to parameters values variation. (Sibanda & Sibanda, 2007) …”
Section: Phasementioning
confidence: 99%
“…SPC methods, such as the CUSUM, have been applied many times in different fields of health care to monitor mortality or another outcome measure. [7][8][9][10][17][18][19][20][21][22] However, for most interventions, the outcome measure in itself is not sufficient to enable evaluation of results, and risk adjustment using risk factors is required. 2 This means changes in both the outcome as well as in patient severity (ie, the risk factors) influence the benchmarking results.…”
Section: Importance Of Surveillancementioning
confidence: 99%
“…In health care, some of these techniques have already been opted for the monitoring of outcomes, for example, cumulative sum (CUSUM) techniques in cardiac surgery. [7][8][9][10] However, to our knowledge, we are the first to describe the use of SPC techniques in their use to monitor risk factors in clinical databases.…”
mentioning
confidence: 99%
“…However, a critical change-point is the point where a major shift in the trend is recognised. There are several approaches to performing a trend analyses and 'changepoint analyses' (Page, 1955;Chow, 1960;Page, 1957;Hinkley, 1971;Hinkley and Schechtman, 1987;Pettitt, 1980;Box and Luceño, 1997;Sibanda and Sibanda, 2007;Fujisaki et al 2008;Taylor, 2000a;Taylor, 2011 Here, the CUSUMs are not the CUSUMs of the values instead they are the CUSUMs of differences between the values and the average. "These differences sum up to zero, so the CUSUM always ends at zero (S43=0)" (Taylor, 2000a).…”
Section: Stages Of Socioeconomic Transitionmentioning
confidence: 99%
“…According to the results of this particular technique in our study, we have not found absolute convergence yet, in any of the indicators selected in this study. Reply: There are several approaches to perform a trend analyses and 'changepoint analyses' (Page, 1955;Chow, 1960;Page, 1957;Hinkley, 1971;Hinkley and Schechtman, 1987;Pettitt, 1980;Box and Luceño, 1997;Sibanda and Sibanda, 2007;Fujisaki et al 2008;Taylor, 2000a;Taylor, 2011). The Chow test is a statistical and econometric test of whether the coefficients in two linear regressions on different data sets are equal or The Chow test, commonly used in econometrics to test for structural breaks.…”
Section: Replymentioning
confidence: 99%